Homosexual Identity in Alex Sanchez's 'Rainbow Trilogy' - Nanda Vidyastria (Lensa: Kajian Kebahasaan, Kesusastraan, dan Budaya, 2017)
This research aims at describing 1) stages of homosexual identity development in three main characters in the Rainbow Trilogy using Cass model, 2) factors influencing the development of homosexual identity using D Augellis theory, and 3) forms of victimization towards homosexuals experienced by the main characters using theories of D Augelli and Rivers. Queer studies was applied to describe and analyze the data in forms of words, phrases, sentences, statements, dialogues as well as monologues in the Rainbow Trilogy, recording thoughts and actions by the characters in accordance with the research focus. As a result, the research finds out that the three novels describe clearly all stages of Cass model of homosexual identity development in Jason and Kyle, including their identity confusions, comparisons, acceptances, tolerances, prides and syntheses. In Nelson, only one stage that can be identified as Nelson is described as one whose sexual identity has been formed. The research also reveals how factors of personal subjectivity and action, interactive intimacy and sociohistorical connection are connected to each others and also influencing the homosexual identity developments of the main characters. Besides, the research also shows that various kinds of victimization occur to Jason, Kyle and Nelson. Normative victimizations made to feel different are experienced by Nelson and Kyle. Family stressor and prejudices in connection to AIDS are experienced by the three characters. Victimization of direct attacks in forms of verbal and physical abuses are experienced by Kyle and Nelson. Lastly, the research finds out that Nelson is the only character experiencing sexual abuse. It occurs in form of undesired comments oriented to a sexual violence.